Knowledge of private dentists in district 5 Manila about biologic width in human periodontium and its significance in restorative dentistry - Bojare, Estrella Marie B.; De Leon, Estrella Marie B.; Karganilla-Frange, Melanie Ruth. (Manila Department of Community Dentistry, University of the Philippines Manila, 2016)
INTRODUCTION: Biologic width is an important physiologic dimension that has been well-documented in literature. Research studies have been consistent about factors that can potentially violate this important anatomic space. Utmost emphasis was given on the importance of margin placements of crowns and other restorative treatments and yet, violations to the biologic width are still often committed by general practitioners. Thus, this study attempts to gauge and assess the knowledge and understanding of dentists regarding biologic width in general, and specifically its significance, preservation and the consequences once iatrogenic violations have been done
METHODS: 70 private dentists in District 5 Manila were asked to answer a 20-item questionnaire about biologic width and its significance through door to door visitation. Results of the test questionnaires were tabulated using Microsoft Word and Excel.
RESULTS: The 70 respondents yielded a mean percentage of 70% (mean score of 7) on Part A which pertained to questions about basic knowledge of biologic width. On the other hand, a mean percentage of 60% (mean score of 6) was gathered on Part B which pertained to questions about knowing biologic width?s significance. In totality, a mean score of 13 (65%) was yielded from the 20-item questionnaires gathered from the 70 participants.
CONCLUSION: The researchers have deduced inconsistencies on knowledge about biologic width in comparison to knowing its significance. The participants have been found to have more knowledge about the basic information on biologic width than its significance in terms of clinical application especially on how it should be preserved, and corrected or reestablished once violations have been done.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dentist; Dentist-patient relations